Effect of physical and chemical mutagens on soybean - Wakode2, Geeta P. Patil1; Manish M. (Current Botany, 2011)
Two varieties of soybean (Glycine max (L) Merill) viz., JS-335 and PKV-1 were treated with various doses of physical (gamma rays) and chemical (EMS) mutagens. A dose dependent decrease was noticed in most of the characters like plant survival germination. The maximum reduction was found in higher doses of mutagens in both the cultivars, while increased pollen sterility was associated with the corresponding increase in doses of mutagens. Results indicated that higher doses were more effective in all the three generations (M1, M2, and M3). However the M1 showed more pronounced reduction in germination and survival than M2 and M3. The increase in pollen sterility was more in cv. PKV-1 indicating its more sensitivity as compared to cv. JS-335.